India`s reluctant urbanization: Thinking beyond - Tiwari, Piyush; Nair, Ranesh; Ankinapalli, Pavan; Rao, Jyoti; Hingorani, Pritika; Gulati, Manisha (London Palgrave macmillan, 2015)
Given the expected scale of the urban transformation in India over the next few years and the time span within which this will occur, this study presents a crucial analysis of the challenges facing 'urban' India. Through a close examination of India's policies, economic system, social systems and politics, it explores the numerous perspectives and debates on India's urbanization.
Keywords: Cities and towns India; Urbanization India; Geography